A Comparison of Surgical Complications in Patients Undergoing Delayed versus Staged Tissue-Expander and Free-Flap Breast Reconstruction. Issue 3 (September 2021) - Shammas, Ronnie L.; Cason, Roger W.; Sergesketter, Amanda R.; Glener, Adam D.; Broadwater, Gloria; Hollins, Andrew; Le, Elliot; Marks, Caitlin; Atia, Andrew N.; Orr, Jonah P.; Hollenbeck, Scott T.
Abstract : Background: Patients undergoing mastectomy may not be candidates for immediate free-flap breast reconstruction because of medical comorbidities or postmastectomy radiation therapy. In this setting, flap reconstruction may be intentionally delayed or staged with tissue expander placement ("delayed-immediate" reconstruction). The optimal reconstructive choice and incidence of complications for these approaches remain unclear. Methods: The authors retrospectively identified patients who underwent delayed [ n = 140 (72 percent)] or staged [ n = 54 (28 percent)] abdominal free-flap breast reconstruction between 2010 and 2018 and compared the incidence of postoperative complications. Results: Patients undergoing staged reconstruction had a higher overall incidence of perioperative complications, including surgical-site infection (40.7 percent versus 6.5 percent; p < 0.001), wound healing complications (29.6 percent versus 12.3 percent; p = 0.004), hematoma (11.1 percent versus 0.7 percent; p < 0.001), and return to the operating room (27.8 percent versus 4.4 percent; p < 0.0001). These complications occurred predominately during the expansion stage, resulting in an 18.5 percent ( n = 10) rate of tissue expander failure. Mean time from mastectomy to flap reconstruction was 476.8 days (delayed, 536.4 days; staged, 322.4 days; p < 0.001). At the time of flap reconstruction, there was no significant difference in the incidence of complications between the staged cohort versus the delayed cohort, including microsurgical complications (1.9 percent versus 4.3 percent; p = 0.415), total flap loss (0 percent versus 2.1 percent; p = 0.278), or fat necrosis (5.6 percent versus 5.0 percent; p = 0.875). Conclusions: The aesthetic and psychosocial benefits of staged free-flap breast reconstruction should be balanced with the increased risk of perioperative complications as compared to a delayed approach. Complications related to definitive flap reconstruction do not appear to be affected by the approach taken at the time of mastectomy. Clinical Question/Level of Evidence: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.